Crassispira (Crassispirella) tuckerana, a replacement name for Crassispira (Crassispirella) tuckeri Bonfitto & Morassi, 2004 (Gastropoda: Turridae: Crassispirinae) not Crassispira tuckeri Le Renard, 1994 - Bonfitto, A.; Morassi, M. (Zootaxa, 2011)
Bonfitto & Morassi (2004) described Crassispira (Crassispirella) tuckeri based on Recent material from Muqdisho, Somalia. Crassispira tuckeri, however, was first proposed by Le Renard (1994) as a new name for Pleurotoma dubia Deshayes, 1835, a Middle Eocene species from France, a homonym of Pleurotoma dubia Cristofori & Jan, 1832. Additionally, no potentially valid synonyms are available for Crassispira (Crassispirella) tuckeri Bonfitto & Morassi, 2004 (ICZN Art. 60.2). Thus, in accordance with Article 60.3 of the International Code of Zoological Nomenclature (1999), a replacement name for Crassispira (Crassispirella) tuckeri Bonfitto & Morassi, 2004 is required.